Analisis Pengaruh Suku Bunga Dan Inflasi Terhadap Nilai Tukar Rupiah Era Pemulihan Ekonomi Pasca Covid 19 Di Indonesia - Annisa Karimah Karimah; Tuti Anggraini; Nuri Aslami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was designed to determine the influence of interest rates and inflation on the exchange rate in the post-Covid-19 economic recovery era in Indonesia. The research method used is quantitative using secondary data taken from the official BI website. The data used are exchange rates, interest rates and inflation from January 2019 to December 2022 on a monthly basis. To test this data, the multiple linear regression method was used. The results of this research show that the research results show that the calculated F value is 11.104 with an F table value of 2.901 so that the calculated F is greater than the F table (11.104 > 2.901). Analysis of the calculation results above also shows that sig. = 0.000 < 0.05, so it can be concluded that Interest Rates and Inflation have a significant simultaneous effect on the Exchange Rate. partially interest rates and inflation have a significant effect on the exchange rate.